2019
DOI: 10.4054/demres.2019.40.20
|View full text |Cite
|
Sign up to set email alerts
|

Who leaves, who stays? Gendered routes out of the family home following union dissolution in Italy

Abstract: This study focuses on couples in Italy who experienced union dissolution between 2005 and 2014 and investigates the existence of gendered routes out of the family home upon separation. METHODS The empirical analyses rely on microdata from the EU Statistics on Income and Living Conditions. Using logistic regression, I estimate whether the likelihood that women move out of the family home upon separation is associated with contextual characteristics, the gender balance within couples, and the presence of childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Previous research found that women are more likely to leave the joint home at separation than men although this seems to reverse when children are present (Ferrari et al 2019;Fiori 2019;Mulder and Malmberg 2011;Mulder and Wagner 2010;Stone et al 2014). Additionally, women were found to be more likely to move from owner-occupied to rental dwellings than men in the Netherlands (Feijten 2005), a finding attributed to the generally lower socio-economic independence of women.…”
Section: Gender Differences In Separation and Elevated Residential Momentioning
confidence: 96%
“…Previous research found that women are more likely to leave the joint home at separation than men although this seems to reverse when children are present (Ferrari et al 2019;Fiori 2019;Mulder and Malmberg 2011;Mulder and Wagner 2010;Stone et al 2014). Additionally, women were found to be more likely to move from owner-occupied to rental dwellings than men in the Netherlands (Feijten 2005), a finding attributed to the generally lower socio-economic independence of women.…”
Section: Gender Differences In Separation and Elevated Residential Momentioning
confidence: 96%
“…In general, women are more likely to move out of the joint home after separation than men (Dewilde 2008;Feijten 2005;Mulder 2013). If the ex-couple has children, men are somewhat more likely to leave the family home than women (Thomas, Mulder, and Cooke 2017a;Fiori 2019). Whether moving or not, the negative financial consequences of separation are more severe for women than for men, which may translate to an unfavourable residential situation (Andreß et al 2006;Feijten 2005;Mulder 2013).…”
Section: Moves Following Separationmentioning
confidence: 99%
“…However, one important result concerns the association of parenthood with LTA duration. As research on separation has shown (e.g., Fiori, ), parenthood seems to structure not only conjugal life but also the ways in which partners separate. Parents make decisions that, from their point of view, may be in the children's best interests.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…From the 1987 to 1988 National Survey of Families and Household (United States) data, he showed that 44% of the ever‐separated women attempted reconciliation. Mulder and Wagner () and Fiori (), for their part, analyzed another key moment in the separation process: the departure from the conjugal home. They looked at which of the two expartners left the family home via an analysis of the costs of decohabitation and the presence of children.…”
mentioning
confidence: 99%